q-hyperelliptic compact nonorientable Klein surfaces without boundary - J. A. Bujalance; B. Estrada (International Journal of Mathematics and Mathematical Sciences)
Let X be a nonorientable Klein surface (KS in short), that is a compact nonorientable surface with a dianalytic structure defined on it. A Klein surface X is said to be q-hyperelliptic if and only if there exists an involution Φ on X (a dianalytic homeomorphism of order two) such that the quotient X/〈Φ〉 has algebraic genus q. q-hyperelliptic nonorientable KSs without boundary (nonorientable Riemann surfaces) were characterized by means of non-Euclidean crystallographic groups. In this paper, using that characterization, we determine bounds for the order of the automorphism group of a nonorientable q-hyperelliptic Klein surface X such that X/〈Φ〉 has no boundary and prove that the bounds are attained. Besides, we obtain the dimension of the Teichmüller space associated to this type of surfaces.